The chemistry of gold extraction - Marsden, John, 1960- (Society for Mining, Metallurgy, and Exploration, 2006)
The Chemistry of Gold Extraction provides the broad base of knowledge now required by all those working in the gold extraction and gold processing industries. The book bridges the gap between research and industry by emphasizing the practical applications of chemical principles and techniques. The technical reference includes in-depth discussions on historical developments; ore deposits and process mineralogy; process selection; principles of gold hydrometallurgy; oxidative pretreatment; leaching; solution purification and concentration; recovery; surface chemical methods; refining; effluent t.
Keywords: Gold -- Metallurgy.; Gold ores.; Hydrometallurgy.; Extraction (Chemistry); elektronické knihy; electronic books